Composition, Structure and Diversity of Species Plant in Dungus Iwul Nature Reserve, Bogor District - Nurkhotimah .; Agus Hikmat; Titiek Setyowati (Media Konservasi, 2017)
The Dungus Iwul Nature Reserve is a conservation area that has been through a series of human and natural disturbance causing to changes in plant species composition and stand structure including its level of diversity.  The purpose of this study was to investigate vegetation changes and the presence of Orania sylvicola (Griff.) H. E. Moore which has been reportedly becoming dominant in this forest area. Research was conducted during June 2017 at Dungus Iwul Nature Reserve, Bogor District.  Vegetation analysis and tree profile diagram were used systematic sampling.  The analyzed data were used to determine the Important Value Index (IVI), diversity index, evenness index, and richness index. Results shows that the forest stand composed of 88 plant species dominated by O. sylvicola. Stand structure performs a reserved J-shape curve which is characterized by tree class diameter concentrating in tree of 20-30 cm diameter. The majority of diversity index, evenness index and richness index values of the plant species has decreased.  This condition confirm the current dynamic process of high stand composition changes which is assumed due to the dense abundance of O. sylvicola and many other supporting factors such as the presence of dispersal agent namely Cynopterus titthaecheilus(Temminck, 1825). Canopy gap due to disturbance enables bats to disperse seed of O. sylvicola, a tolerant species that has a remote tubular sprouting types (cotyledon and seed separated by tubular section) and help this plant species to grow over the pioneer species. These elements causes to the growth and spread of O. sylvicola which is later disturbed the vegetation surrounding and tended to be invasive.  Keywords: Cagar Alam Dungus, diversity, stand structure and composition